"2-Amino glucose" as a substrate for synthesis of magnetically recoverable nanocatalyst NiFe2O4@SiO2@amino glucose for the green synthesis of novel bis (1, 2-dihydro-4-hydroxy-2-oxoquinolin-3-yl)methanes. (1st September 2019) - Aghazadeh, Behnaz; Nikpassand, Mohammad
Abstract: 2-Amino glucose (( 2S, 3R, 4S, 5S, 6R )-2-amino-6-(hydroxymethyl)tetrahydro- 2H -pyran-3, 4, 5-triol) as a substrate for the synthesis of NiFe2 O4 @SiO2 @amino glucose supply an environmentally friendly procedure for the synthesis of bis(1, 2-dihydro-4-hydroxy-2-oxoquinolin-3-yl)methanes through one-pot condensation of aldehyde or pyrazolo carbaldehyde and two equivalents of 4-hydroxyquinolin-2(1 H )-ones in aqueous media. Eco‐friendliness, high purity of the desired products, short reaction time and easy workup procedure can be mentioned as the other advantages of this method. The structures of the synthesized 4-hydroxy-2(1 H )-quinolone compounds were confirmed by 1 H, 13 C NMR and FTIR spectral data and elemental analyses. Graphical abstract: Image 1 Highlights: NiFe2O4@SiO2@amino glucose as a catalyst from 2-Amino glucose as a substrate. Green synthesis of novel bis (2-oxoquinolin-3-yl)methanes in aqua media. All of were characterized by IR, NMR and elemental analysis. Environmental friendliness and shorter reaction time are some of advantages of this reaction.